Needs and Nonviolent Communication in the Religious Studies Classroom - Agnew, Elizabeth N. (Teaching theology and religion, 2012)
Religious studies classrooms are microcosms of the public square in bringing together individuals of diverse identities and ideological commitments. As such, these classrooms create the necessity and opportunity to foster effective modes of conversation. In this essay, I argue that communication attuned to shared human needs – among them needs for safety, respect, and belonging – offers a transformative response to the potential self-silencing and peer-conflict to which religious studies classrooms are prone. I develop this claim with reference to the research on teaching religious studies conducted by Barbara Walvoord and the pedagogy of theologian and Swarthmore University President Rebecca Chopp in formulating an “ethics of conversation” with her students. Building on this foundation, I make a case for developing an “ethos of conversation” in the religious studies classroom based on psychologist and peace activist Marshall Rosenberg's method of “nonviolent communication.” While addressing the roles of conflict and toleration in the classroom through the perspectives of Alasdair MacIntyre and Jeffrey Stout, I argue that Rosenberg's approach to communication is a powerful asset to education that models constructive engagement in the macrocosm of civic life.